2006
DOI: 10.1074/jbc.m508382200
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Ceramidase Encoded by the Asah2 Gene Is Essential for the Intestinal Degradation of Sphingolipids

Abstract: Complex sphingolipids are abundant as eukaryotic cell membrane components, whereas their metabolites, in particular ceramide, sphingosine, and sphingosine 1-phosphate, are involved in diverse cell signaling processes. In mammals, degradation of ceramide by ceramidase yields sphingosine, which is phosphorylated by the action of sphingosine kinase to generate sphingosine 1-phosphate. Therefore, ceramidases are key enzymes in the regulation of the cellular levels of ceramide, sphingosine, and sphingosine 1-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
138
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 38 publications
(39 reference statements)
2
138
0
Order By: Relevance
“…Several reports have indicated that alkaline sphingomyelinase is present in the intestinal mucosa (35)(36)(37) and that the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase ( 38,39 ). Neutral ceramidase encoded by Asah2 is also present in the small intestine ( 40 ). We have reported that the hydrolytic activity in the small intestine toward glucosylceramide and ceramide derived from maize is consistent with the fi ndings of such activity toward mammalian-derived sphingolipids ( 26 ).…”
Section: Discussionsupporting
confidence: 75%
“…Several reports have indicated that alkaline sphingomyelinase is present in the intestinal mucosa (35)(36)(37) and that the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase ( 38,39 ). Neutral ceramidase encoded by Asah2 is also present in the small intestine ( 40 ). We have reported that the hydrolytic activity in the small intestine toward glucosylceramide and ceramide derived from maize is consistent with the fi ndings of such activity toward mammalian-derived sphingolipids ( 26 ).…”
Section: Discussionsupporting
confidence: 75%
“…Alkaline sphingomyelinase is present in the intestinal mucosa (25)(26)(27), and the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase (28,29). Neutral ceramidase encoded by Asah2 is also present in the small intestine (30). Previously, we investigated the absorption of dietary glucosylceramide derived from maize into the rat intestine compared with that of glucosyl-N-palmitoylsphingosine and demonstrated that the intact form of sphingadienine was absorbed into the lymph by intestinal cells after administration of maize glucosylceramide.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of neutral ceramidase in ceramide digestion in the gut was recently confirmed by studies on genetargeted mice lacking active neutral ceramidase 2 (17).…”
mentioning
confidence: 77%